Plamen Doynov – Generation and Poetry. 1956–1989 - Алипиева, Антоанета (Poznańskie Studia Slawistyczne, 2019)
The article deals with Plamen Doynovʼs idea of the poetic generations during the time of the socialism. There are the connections between the administrative power and the poets, between the ideological directives and the poetry as an autonomous area. The author suggests the idea of the periodization within poetry during the socialism.